Korean influence in the beginning period of Japan's Buddhist Arts - Tran, Ngoc Them (Đại học Quốc gia Hà Nội, 2020)
The abobe mentioned works can be seem as basic works in the beginning period of Japanese Buddhist arts imported from Korea or deeply influenced by Korean style. All aspects relating to these works are presented and analysed convincingly through relialbe historical materials and plentiful source of pictures by the author